Development of a Prescription Screening System in an In-patient Department, Banpong Hospital - ฉัตรไพฑูรย์, บุญสุชิน (Hua Hin Medical Journal, 2021)
Background: A medication error is any preventable event that may cause or lead to inappropriate medication use or patient harm. The largest discrepancies in prescribing was found compared to other procedures which can be prevented using a drug order screening system to find and correct more pre-patient drug discrepancies. Objectives: To develop a prescription screening system for an In-patient section, and to compare the prescribing error reports before and after prescription screening system was implemented. Methods: This action research proceed as follows ​1. Analysis of medication errors problem 2. Develop a screening system for inpatient drug orders, which can be divided into 2 phases: creating a screening form for drug orders, and adding a procedure for pharmacists to screen prescriptions before recording drug information in the system 3. Summarized the results and evaluated the outcome by comparing the prescribing errors before and after prescription screening system implementation. The descriptive statistics was used in data analysis. Results: The results showed that prescribing errors were detected increased from 2.93 to 6.16 times per 1,000 patient-days. when using the developed drug prescription screening form. And the discrepancy can be detected 11.35 times per 1,000 patient-days when adding pharmacists to screen the drug orders in the step before recording drug orders in the computer system especially medication errors that affect the clinical outcome of the patient. The first three types of prescribing error found were non-prescribing, improper dosage prescription and wrong method or wrong injection appointment. Conclusions: A system was developed by adding pharmacists to screen prescriptions with the drug order screening form in the process of pre-recording drug orders on a computer. It can better prevent discrepancies from prescriptions before reaching the patient.